A Review of Using Mathematical Modeling to Improve Our Understanding of Bacteriophage, Bacteria, and Eukaryotic Interactions - Styles, Kathryn M.; Brown, Aidan T.; Sagona, Antonia P. (Frontiers in Microbiology, 2021)
Phage therapy, the therapeutic usage of viruses to treat bacterial infections, has many theoretical benefits in the ‘post antibiotic era’. Nevertheless, there are currently no approved mainstream phage therapies. One reason for this is a lack of understanding of the complex interactions between bacteriophage, bacteria and eukaryotic hosts. These three-component interactions are complex, with non-linear or synergistic relationships, anatomical barriers and genetic or phenotypic heterogeneity all leading to disparity between performance and efficacy in in vivo versus in vitro environments. Realistic computer or mathematical models of these complex environments are a potential route to improve the predictive power of in vitro studies and to streamline lab work. Here, we review the current status of mathematical modelling and highlight that data on mutational stochasticity, time delays and population densities could be critical in the development of realistic phage therapy models. With this in mind, we aim to inform and encourage the collaboration and sharing of knowledge and expertise between microbiologists and theoretical modellers, smoothing the road to regulatory approval and widespread use of phage therapy.